Highly Reliable Trust Establishment Scheme in Ad-Hoc Networks - REN, K. (Institutional Knowledge at Singapore Management University, 2004)
Securing ad hoc networks in a fully self-organized way is effective and light-weight, but fails to accomplish trust initialization in many trust deficient scenarios. To overcome this problem, this paper aims at building well established trust relationships in ad hoc networks without relying on any pre-defined assumption. We propose a probabilistic solution based on distributed trust model. A secret dealer is introduced only in the system bootstrapping phase to complement the assumption in trust initialization. With it, much shorter and more robust trust chains are able to be constructed with high probability. A fully self-organized trust establishment approach is then adopted to conform to the dynamic membership changes. The simulation results on both static and dynamic performances show that our scheme is highly resilient to dynamic membership changing and scales well. The lack of initial trust establishment mechanisms in most higher level security solutions (e.g. key management schemes, secure routing protocols) for ad hoc networks makes them benefit from our scheme.